Krisis Pangan di Yaman Sebagai Ancaman Keamanan Non-Tradisional: Analisis Ketergantungan terhadap Bantuan Internasional - Rameyza Mauli Fatiha (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The food crisis in Yemen is one of the largest humanitarian crises in the world. This issue is caused by prolonged conflict, economic instability, and disruptions in food production and distribution systems. This study aims to analyze the food crisis in Yemen as a non-traditional security threat, examine the role of international assistance, and assess the potential for dependency through the perspective of Dependency Theory. The findings indicate that the food crisis in Yemen is not merely an economic issue but also a threat to Human Security, as it hinders the fulfillment of the population’s basic needs. In this situation, international organizations such as the World Food Programme and the United Nations Children’s Fund play significant roles through food assistance, nutrition programs, healthcare services, and protection for vulnerable groups. However, reliance on international aid has the potential to reinforce dependency relationships between recipient countries and donor actors. From the perspective of Dependency Theory, international assistance may alleviate the crisis in the short term, but it does not fully address the root causes of the food crisis. Therefore, strengthening domestic capacity and achieving food self-sufficiency are necessary as long-term solutions.